The Regional Differentiation on Poverty in East-European Countries - Alfiya Nizamova (Luxembourg Income Study (LIS), 1997)
The topic of this paper is country comparisons of regional differences in poverty and inequality profiles. Four Eastern-European countries were examined in the final analysis: Czech Republic, Poland, Slovakia, and Russia.
Keywords: 330; Regionale Einkommensverteilung; Armut; Osteuropa